The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00384-021-03891-0
|View full text |Cite
|
Sign up to set email alerts
|

A global systematic review and meta-analysis on laparoscopic vs open right hemicolectomy with complete mesocolic excision

Abstract: Purpose The aim of this study was to compare the outcomes of right hemicolectomy with CME performed with laparoscopic and open surgery. Methods PubMed, Scopus, Web of Science, China National Knowledge Infrastructure, Wanfang Data, Google Scholar and the ClinicalTrials.gov register were searched. Primary outcome was the overall number of harvested lymph nodes. Secondary outcomes were short and long-term course variables. A meta-analysis was performed to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Colon cancer is one of the most common malignant tumors in digestive tract, the morbidity and mortality are increasing year by year, and so far surgery remains the mainstream curative treatment for colon cancer. [1][2][3] Postoperative pain can delay the wound healing, the first ambulation and the recovery of intestinal tract, leading to the patient's body in a stress status, which results in the damage of immune function, thus promoting the recurrence and metastasis of tumor after surgery, and delaying the overall postoperative recovery speed. [4][5][6][7][8][9][10][11][12] It has been demonstrated that scientific and reasonable pain management is helpful to reduce complications and accelerate the recovery of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer is one of the most common malignant tumors in digestive tract, the morbidity and mortality are increasing year by year, and so far surgery remains the mainstream curative treatment for colon cancer. [1][2][3] Postoperative pain can delay the wound healing, the first ambulation and the recovery of intestinal tract, leading to the patient's body in a stress status, which results in the damage of immune function, thus promoting the recurrence and metastasis of tumor after surgery, and delaying the overall postoperative recovery speed. [4][5][6][7][8][9][10][11][12] It has been demonstrated that scientific and reasonable pain management is helpful to reduce complications and accelerate the recovery of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The first report on laparoscopic right colectomy appeared in 1991 and after only 1 year, laparoscopic right hemicolectomy with intracorporeal ileocolic anastomosis (ICA) was described 27 . Recent results confirm that L‐CME is a safe and effective alternative associated with excellent oncologic outcomes and acceptable complications 9,15,28,29,30,31 . In our experience, the choice of performing O‐CME plus CVL or L‐CME plus CVL strongly depends on emergency setting and preanesthetic evaluation.…”
Section: Discussionmentioning
confidence: 89%
“…In other terms, CME plus CVL is an ‘en‐bloc’ removal of primary tumour with adequate resection margins including areas of lymphatic drainage within an intact envelope of peritoneum 7 . CME improves oncological outcome 6,8,9,10 . Although the initial Italian experience documented a poor prognosis after curative right hemicolectomy for CC adenocarcinomas with 5‐year survival rate of 57%, recent results show that laparoscopic right hemicolectomy might be performed safely with a better prognosis and a 5‐year survival rate of 75% 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The AL rate varies widely and depends on the anatomic location of the anastomosis. The reported AL rate after laparoscopic ICR and right hemicolectomy ranges from 1 to 2.6% ( 29 31 ), whereas the AL rate after only laparoscopic AR without defunctioning stoma ranges from 6% to more than 10% ( 32 34 ). In the present study, the AL rate was 7.7% after AR, which is similar to the rate reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%